Transportation Economics / A Guide to Information Sources (Gale Research Company, 1976)
Acknowledgements, Introduction, General Transportation, Railroads, Highway Transportation, Air Transoprtation, Water Transportation, Business Logistics, Urban Transportation, Additional Sources of Information, Author Index, Title Index, Subject Index.